The Effect of Exclusive Breastfeeding on Mother's Weight Retention in Postpartum Period - Ayut Merdikawati; Laily Yuliatun; Muladefi Choiriyah; Devi Hana Purnama Sari; Rani Diana Balqis (Journal of Social Research, 2023)
Exclusive breastfeeding is giving only breast milk to babies, without other drinks food, or water, except for oral rehydration fluids, drops, or syrup containing vitamins, mineral supplements, or drugs recommended by health workers for medical reasons. Breast milk contains complete nutrition which is very good for growth and development and is easily digested by babies. Mothers who exclusively breastfeed find it easier and faster to lose weight to their pre-pregnancy state. As the gestational age increases, there is a progressive accumulation of maternal body fat. These fat reserves are a source of energy that will be used in the process of producing breast milk. By breastfeeding, the body will produce more breast milk so that fat deposits that function as energy reserves will be used. Thus shrinking fat deposits, the mother's weight will quickly return to its pre-pregnancy state. At present, postpartum weight gain is a separate problem for mothers because of frequent postpartum weight retention. The purpose of this study was to determine the effect of exclusive breastfeeding on maternal weight in the postpartum period. A research design used in this study is the pretest-posttest control group design. This study used a group of mothers who exclusively breastfed and a group of mothers who did not exclusively breastfeed as a control group. Data on exclusive and non-exclusive breastfeeding were taken using a questionnaire, while the mother's weight immediately after delivery was taken from the mother's KMS or health worker documents. Calorie intake data was taken using the semi-SSQ questionnaire. While data on body weight in the range of 0-6 months, was taken by way of the researcher weighing directly using the same scales for each respondent. research results obtained Exclusive breastfeeding on mothers causing maternal weight loss in the first 6 months postpartum. Weight retention did not occur as in the non-exclusive breastfeeding group.